Generative pre-trained transformers: ‘Ctrl+alt+create’ or ‘ctrl+alt+delete’ for IT education? - Samer Abaddi (Journal of Ethics in Entrepreneurship and Technology)
Graphical abstract – Purpose – This study aims to investigate different traits of generative pre-trained transformer (GPT) in information technology (IT) students’ enhancement of coding skills within Jordanian undergraduate education. These characteristics are perceived customization, simulations, usefulness, ease of use, risks and complexity. Design/methodology/approach – Using a quantitative research design, this study analyzes data from a survey of IT undergraduate students interacting with GPT-based coding tools and simulations (Three filtration steps). Structural equation modeling (SEM) is used to assess the relationships between GPT attributes and coding skill enhancement outcomes, providing a robust examination of the theoretical models proposed. Findings – The findings reveal that perceived customization, generated simulations, ease of use and usefulness of GPT models significantly positively affect coding skills enhancement (CSE). In contrast, complexity and perceived risks are found to negatively impact these outcomes. Practical implications – This study underscores the necessity for educators, curriculum designers and technology developers to prioritize the ease of use and customization capabilities of GPT tools to enhance coding experiences. Organizations must ensure robust data security measures to protect user data and build trust. An international body/commission should be launched to regulate the AI industry (including GPT) and ensure adherence to ethical and privacy standards. Originality/value – Exploring perceived customization, usefulness and ease of use in addition to highlighting potential drawbacks, such as complexity and perceived risks, calls for improved security measures and ethical standards in AI education and application. The study also contributes to the growing body of knowledge on the application of AI in IT education by linking two robust frameworks to explore GPT aspects of CSE.